Undermining the foundation: a brief overview of the effects of a widespread invader on coastal ecosystem engineers - Bissett, William G.; Ramey-Balci, Patricia A.; Quijón, Pedro A. (Frontiers in Marine Science, 2025)
By creating habitats or influencing the immediate physical environment, ecosystem engineers shape the diversity, function and services provided by ecosystems. Thus, the disruption of these species is relevant given their broad influence on native communities and ecosystems. As such, we review the effects (positive, negative, or neutral) of a widespread invasive species, the European green crab (Carcinus maenas) on key coastal ecosystem engineers. We examined the literature and focused on 53 published studies to assess reported impacts on well-known macrophytes, mussels, oysters and clams. Despite the wide range of response variables measured and reported, green crab effects were overwhelmingly negative. These effects were mediated by direct (through consumption and sediment burrowing) or indirect mechanisms (through seed consumption, alteration of habitat quality or effects on related species), and were often context dependent. These conclusions are limited by ongoing green crab expansions where possible impacts have not been yet documented, and by cases of neutral or minor impacts that remain unpublished. Green crab effects often result in disruption rather than the loss of local ecosystem engineers, but they clearly add to the ongoing effects of other global stressors.